Variation and trends in dough rheological properties and flour quality in 330 Chinese wheat varieties - Xiushi Yang; Li Wu; Zhihua Zhu; Guixing Ren; Sancai Liu (Crop Journal, 2014)
The objective of this study was to investigate variation and trends in dough rheological properties and flour quality traits in 330 Chinese wheat varieties. The dough rheological properties of development time (DT), stability time (ST), and farinograph quality number (FQN) were evaluated, as well as the flour quality traits of protein (PC), wet gluten content (WGC), and sedimentation value (SV). The coefficients of variation of DT (40.5%), ST (58.1%), and FQN (42.4%) were higher than those of PC (9.1%), WGC (10.1%), and SV (15.3%). Normal distributions were observed for the flour quality indices but not for the rheological parameters. SV was strongly correlated with the three rheological parameters and accordingly might be used as a primary indicator for dough rheological property evaluation. Our results showed that there has been marked improvement in dough rheological properties for Chinese wheat varieties released since 1986, while flour quality has remained stable.